2007
DOI: 10.1111/j.1582-4934.2007.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine effects of transplanted myoblasts and relaxin on post‐infarction heart remodelling

Abstract: In the post-infarcted heart, grafting of precursor cells may partially restore heart function but the improvement is modest and the mechanisms involved remain to be elucidated. Here, we explored this issue by transplanting C2C12 myoblasts, genetically engineered to express enhanced green fluorescent protein (eGFP) or eGFP and the cardiotropic hormone relaxin (RLX) through coronary venous route to swine with experimental chronic myocardial infarction. The rationale was to deliver constant, biologically effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
90
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(98 citation statements)
references
References 36 publications
8
90
0
Order By: Relevance
“…While relaxin's major mode of action in the infarct model appeared to be its antifibrotic capability, its added capacity to reduce cardiomyocyte apoptosis, while promoting blood vessel growth suggests that relaxin may hold promise as an agent for the treatment of coronary artery disease including MI. Specifically, relaxin's effects seen in the infarct model might also be complementary to cell-based therapies in this setting, which is consistent with the recent findings of Bani and colleagues in pig 14 and rat 42 models of MI, demonstrating that transplanted myoblasts genetically engineered to express relaxin at the site of cell engraftment reduced post-infarct collagen density, while increasing markers of vascularization and cardiac function. Progress in cell-based therapies has been hampered by a very low viability of implanted stem cells, insufficient nourishment and fibrotic environment of the host, poor functional coupling with viable host cardiomyocytes, and incomplete differentiation.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…While relaxin's major mode of action in the infarct model appeared to be its antifibrotic capability, its added capacity to reduce cardiomyocyte apoptosis, while promoting blood vessel growth suggests that relaxin may hold promise as an agent for the treatment of coronary artery disease including MI. Specifically, relaxin's effects seen in the infarct model might also be complementary to cell-based therapies in this setting, which is consistent with the recent findings of Bani and colleagues in pig 14 and rat 42 models of MI, demonstrating that transplanted myoblasts genetically engineered to express relaxin at the site of cell engraftment reduced post-infarct collagen density, while increasing markers of vascularization and cardiac function. Progress in cell-based therapies has been hampered by a very low viability of implanted stem cells, insufficient nourishment and fibrotic environment of the host, poor functional coupling with viable host cardiomyocytes, and incomplete differentiation.…”
Section: Discussionsupporting
confidence: 77%
“…The relaxin-induced remodeling of scar healing in this model are also consistent with its anti-fibrotic effects demonstrated in larger experimental models, 14 and with the progressive cardiac fibrosis phenotype demonstrated in ageing relaxin-deficient mice, with resultant ventricular diastolic dysfunction. 21 The anti-apoptotic effects of relaxin in the infarcted murine heart are also consistent with its effects in a porcine model of MI, 36 and its ability to protect cardiomyocytes from apoptosis in vitro; 16 while its pro-angiogenic Relaxin remodels post-infarct fibrotic healing CS Samuel et al effects are in keeping with that observed in the pig model of MI.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…It is now believed that functional improvement results from neovascularisation and the restoration of blood fl ow to ischaemic muscle, and that this phenomenon is initiated, maintained, and enhanced by paracrine factors and secondary recruitment of progenitor cells (Cho et al, 2007;Formigli et al, 2007).…”
Section: Introductionmentioning
confidence: 99%